The influence of time management behaviours before starting general physics laboratory-I experiments on academic achievement in the course - Erdemir, Mustafa; Tomar, Hurmus (Birlesik Dunya Yenilik Arastirma ve Yayincilik Merkezi, 2019)
The purpose of this study is to determine the time management behaviours before starting experiments in the laboratory environment and to find out whether such behaviours are influential on academic achievement in the laboratory course. Nine pre-service science teachers were observed for 9–11 minutes per week before starting experiments for 6 weeks. The findings were obtained through analysis of observation records and the time management behaviours before starting experiments by two domain experts. The pre-service teachers reading experiment leaflets prior to experiments were found to have a higher academic achievement level compared to those not reading them. In addition, a positive relationship was identified between academic achievement and the time management behaviour involving having textbooks, lecture notes and other sources about subjects present before experiments. Getting tools and materials before experiments, organising experiment desks, cooperation with groupmates and having experiment leaflets present were also found to influence academic achievement. Keywords: Time management, academic achievement, general physics laboratory-I, pre-service science teachers.
Keywords: 4. Education